Novel copper-tellurium alloy for new energy field and low-cost preparation method of novel copper-tellurium alloy

By adding a specific proportion of Ce and Zr elements to the copper tellurium alloy and adopting a low-cost preparation process, the TeZrCe phase is made small and diffusely distributed, solving the problem of complex and high cost of the existing copper tellurium alloy preparation process, achieving efficient and low-cost copper tellurium alloy preparation, improving the conductivity and plasticity of the material.

CN119592838APending Publication Date: 2025-03-11CENT SOUTH UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411780465.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing copper tellurium alloys have complex processes during the preparation process, consume a lot of electrical energy, and generate pollution, low production efficiency and high cost, and the distribution of its second phase in the copper matrix is ​​not conducive to plasticity.

Method used

The composition of copper tellurium alloys is improved by using Ce and Zr elements of a specific proportion, and a new copper tellurium alloy is prepared through smelting, casting, homogenization and combined deformation heat treatment processes, so that the TeZrCe phase is small and diffusely distributed to adapt to cold processing deformation.

Benefits of technology

It significantly improves the conductivity, tensile strength and plasticity of copper tellurium alloy, reduces the preparation cost, is suitable for industrial production, and the method is simple and the equipment requirements are low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592838A_ABST
    Figure CN119592838A_ABST
Patent Text Reader

Abstract

The invention relates to a novel copper-tellurium alloy for the field of new energy and a low-cost preparation method of the novel copper-tellurium alloy, the copper-tellurium alloy material comprises the following components: 0.2-1.5 wt% of Te, 0.1-0.75 wt% of Ce, 0.09-0.6 wt% of Zr, less than or equal to 0.02 wt% of P and the balance of Cu, and the preparation method comprises smelting, casting, homogenization and combined thermomechanical treatment processes. The Zr element with a specific proportion is added into the alloy, so that Te and Zr are combined to form a primary phase with a smaller radius, the characteristic that a second phase of a traditional copper-tellurium alloy is distributed along crystals is remarkably improved, and the plasticity of the copper-tellurium alloy is greatly improved. By adding the Ce element, the TeZr phase and binding energy can be further reduced, stable distribution of new-phase TeZrCe is promoted, the TeZrCe alloy can be prepared through cold machining deformation, the alloy production efficiency is improved, meanwhile, the alloy preparation cost is greatly reduced, and the good industrialization prospect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new materials, and in particular relates to a new copper-tellurium alloy for use in the field of new energy and a low-cost preparation method thereof. Background Art

[0002] In recent years, with the continuous development of the field of new energy vehicles, the demand for copper alloys with multiple functions has increased significantly. As new energy vehicles continue to develop towards new technologies such as fast charging and speed increase, copper alloys that have high conductivity and can work safely and stably under large currents have become the key research and development products of new energy vehicle conductor materials. Since the tellurium element is almost insoluble in the copper matrix, the second phase formed in the alloy has a low melting point and high melting enthalpy. Therefore, the copper-tellurium alloy prepared by adding a small amount of tellurium to pure copper not only has high conductivity, but also has high resistance to arc erosion that can adapt to working in a high current environment. Therefore, copper-tellurium alloys are widely used as contact conductor materials for new energy vehicle charging piles, transformers, relays and other devices.

[0003] However, tellurium and copper are almost immiscible. When preparing copper-tellurium alloy, tellurium element will form copper-tellurium composite second phase distributed in the copper matrix. Because the second phase is hard and brittle, and is only distributed at the grain boundaries of the copper matrix, the plasticity of copper-tellurium alloy is extremely poor, which causes great difficulties in processing. In order to improve material utilization and successfully prepare copper-tellurium alloy products, copper-tellurium alloy is prepared by upward continuous casting, continuous casting, hot rolling, hot extrusion and other methods. For example, invention patents CN117568654A and CN116083749A disclose the preparation method using a combination of semi-continuous casting and hot rolling. Patent CN112575217A discloses the preparation of copper-tellurium alloy rods using upward continuous casting. Patent CN110284024B discloses preparation by hot extrusion.

[0004] However, these methods have complicated procedures. The preparation of alloys by hot deformation consumes a lot of electricity, generates a lot of pollution, has low preparation efficiency, and has high industrial production costs. However, with the continuous expansion of the new energy vehicle market, there is an urgent need for a new type of copper-tellurium alloy that can change the distribution law of the second phase in the copper matrix so that it can be finely dispersed in the matrix. This new type of copper-tellurium alloy can adapt to cold deformation, and a matching high-efficiency and low-cost cold deformation preparation process has been developed. Summary of the invention

[0005] In order to solve the above-mentioned deficiencies and shortcomings of the prior art, the present invention aims to provide a new copper-tellurium alloy for use in the new energy field and a low-cost preparation method thereof.

[0006] The technical solution adopted by the present invention is as follows:

[0007] A copper-tellurium alloy for use in the field of new energy consists of the following components: Te: 0.2-1.5wt%, Ce: 0.1-0.75wt%, Zr: 0.09-0.6wt%, P: ≤0.02wt%, and the remainder is Cu.

[0008] Preferably, the copper-tellurium alloy for new energy is composed of the following components: Te: 0.2-1.2wt%, Ce: 0.1-0.5wt%, Zr: 0.1-0.45wt%, P: ≤0.008wt%, and the balance is Cu.

[0009] Preferably, the copper-tellurium alloy has the following properties: electrical conductivity greater than 85.4% IACS, hardness greater than 98 HV, tensile strength greater than 297 MPa, elongation greater than 8.1%, and yield greater than 44.7%.

[0010] Preferably, the copper-tellurium alloy comprises a TeZrCe phase.

[0011] A low-cost preparation method for the new copper-tellurium alloy used in the new energy field, the method comprising smelting, casting, homogenization and combined deformation heat treatment processes.

[0012] As a preference, the method comprises the following steps:

[0013] (1) Melting: Various element components are prepared in proportion according to the alloy composition, the raw materials are added to the crucible, and after being fully stirred under a protective atmosphere, the upper impurities are removed to purify the melt, and the furnace temperature is controlled at 1250-1400°C to obtain a molten copper alloy;

[0014] (2) Casting: pouring the molten copper alloy at a temperature of 1250-1350° C.;

[0015] (3) Homogenization: The copper alloy ingot is subjected to homogenization annealing treatment in a protective atmosphere at a temperature of 700-850°C for 2-5 hours;

[0016] (4) Combined deformation heat treatment: the homogenized ingot is subjected to cold working deformation treatment with a deformation amount of ≥80%; the alloy is then pretreated at 450-550°C for 1-2 hours under a protective atmosphere; then cold deformation treatment with a deformation amount of ≥75% is performed; then aging treatment is performed under a protective atmosphere at a temperature of 300-500°C for 2-16 hours to obtain a copper tellurium alloy for use in the new energy field.

[0017] Preferably, the protective atmosphere is nitrogen.

[0018] The copper-tellurium alloy used in the new energy field is obtained by the above low-cost preparation method.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) Ce and Zr elements are added to the copper-tellurium alloy of the present invention in a specific ratio. Zr element can form TeZr phase with Te, which is not only more conducive to the precipitation of Te in the copper-tellurium alloy, but also significantly improves the conductivity of the copper-tellurium alloy matrix. Moreover, the new phase is more finely dispersed in the copper matrix, which significantly improves the distribution of the original CuTe phase along the crystal, greatly improves the plasticity of the alloy, and makes the alloy adaptable to cold working deformation. The addition of Ce element can further reduce the binding energy of the new phase, and the formed TeZrCe phase is more finely dispersed and more stable. The optimization effect of Ce is only effective for the TeZr phase.

[0021] (2) Corresponding to the product of the present invention, the new copper-tellurium alloy of the present invention can be prepared by cold working deformation, which greatly reduces the preparation cost of the alloy while improving the alloy production efficiency. The new copper-tellurium alloy disclosed in this patent has a good industrialization prospect.

[0022] (3) The copper-tellurium alloy prepared by the present invention has good electrical conductivity and strength. The tensile strength of the alloy prepared by the method is greater than 297 MPa, and the electrical conductivity is greater than 85.4% IACS. The preparation method disclosed by the present invention is simple and has low equipment requirements. It significantly improves the preparation efficiency of the alloy and greatly reduces the production and processing cost of the alloy, which is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0024] Figure 1 The as-cast microstructure in Example 1 of the present application;

[0025] Figure 2 The SEM scan and EDS spectrum of the final state in Example 2 of the present application;

[0026] Figure 3 The SEM scan and EDS energy spectrum diagram of the final state in Comparative Example 2 of the present application. DETAILED DESCRIPTION

[0027] In order to enable those skilled in the art to better understand the technical solutions in the embodiments of the present invention and to make the above-mentioned objects, features and advantages of the present invention more obvious and understandable, the specific implementation modes of the present invention are further described below.

[0028] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0029] Example 1

[0030] Electrolytic copper, pure tellurium, Cu-24Ce master alloy, Cu-13P and Cu-50Zr master alloy are used as raw materials, and the proportions are as follows: Te: 0.8wt%, Zr: 0.4wt%, Ce: 0.2wt%, P: 0.008wt%, and the balance is Cu. In a graphite crucible, the copper is heated and melted using an induction furnace, and the master alloy of the remaining components is added. Finally, element Te is added, and nitrogen is protected. After sufficient stirring, the upper impurities are removed again to purify the melt, and the furnace temperature is controlled at 1300-1400℃. The molten copper alloy is cooled to 1250℃ for casting. The typical cast structure photo of the alloy is shown in the figure. Figure 1 shown.

[0031] Example 2

[0032] Electrolytic copper and pure tellurium, Cu-24Ce master alloy, Cu-13P and Cu-50Zr master alloy are used as raw materials, and the proportions are as follows: Te: 0.4wt%, Ce: 0.1wt%, Zr: 0.2wt%, P: 0.008wt%, and the balance is Cu. In a graphite crucible, the copper is heated and melted using an induction furnace, and the master alloys of the remaining components are added. Finally, the element tellurium is added, and nitrogen protection is applied. After sufficient stirring, the upper impurities are removed again to purify the melt, and the furnace temperature is controlled at 1350-1450°C. When the temperature of the molten copper alloy is cooled to 1250°C, casting is performed. The copper alloy ingot is subjected to homogenization annealing treatment at 800°C for 4h under a protective atmosphere; the homogenized ingot is subjected to cold working deformation treatment with an 80% deformation amount; the alloy is then pretreated at 550°C for 1 hour under a protective atmosphere; and then cold deformation processing with a deformation amount of 80% is performed. Then, aging treatment was carried out under protective atmosphere at a temperature of 500°C for 8 hours; the alloy had a tensile strength of 314 MPa, an elongation of 19%, a conductivity of 95.5% IACS, a hardness of 98 HV, and a material yield of 68.2%.

[0033] Example 3

[0034] Electrolytic copper and pure tellurium, Cu-24Ce master alloy, Cu-13P and Cu-50Zr master alloy are used as raw materials, and the proportions are as follows: Te: 0.2wt%, Ce: 0.15wt%, Zr: 0.1wt%, P: 0.008wt%, and the balance is Cu. In a graphite crucible, the copper is heated and melted using an induction furnace, and the master alloys of the remaining components are added. Finally, the element tellurium is added, and nitrogen protection is used. After sufficient stirring, the upper impurities are removed again to purify the melt, and the furnace temperature is controlled at 1350-1450°C. When the temperature of the molten copper alloy is cooled to 1250°C, casting is performed. The copper alloy ingot is subjected to homogenization annealing treatment at 800°C for 4h under a protective atmosphere; the homogenized ingot is subjected to cold working deformation treatment with an 80% deformation amount; the alloy is then pretreated at 550°C for 1 hour under a protective atmosphere; and then cold deformation processing with a deformation amount of 80% is performed. Then, aging treatment was carried out under protective atmosphere at a temperature of 500°C for 8 hours; the alloy had a tensile strength of 297 MPa, an elongation of 21%, a conductivity of 97.4% IACS, a hardness of 91 HV, and a yield of 66.4%.

[0035] Example 4

[0036] Electrolytic copper and pure tellurium, Cu-24Ce master alloy, Cu-13P and Cu-50Zr master alloy are used as raw materials, and the proportions are Te: 1.2wt%, Ce: 0.45wt%, Zr: 0.5wt%, P: 0.008wt%, and the balance is Cu. In a graphite crucible, the copper is heated and melted using an induction furnace, and the master alloys of the remaining components are added. Finally, the element tellurium is added, and nitrogen is protected. After sufficient stirring, the upper impurities are removed again to purify the melt, and the furnace temperature is controlled at 1350-1450°C. When the temperature of the molten copper alloy is cooled to 1250°C, casting is performed. The copper alloy ingot is subjected to homogenization annealing treatment at 800°C for 4h under a protective atmosphere; the homogenized ingot is subjected to cold working deformation treatment with an 80% deformation amount; the alloy is then pretreated at 550°C for 1 hour under a protective atmosphere; and then cold deformation processing with a deformation amount of 80% is performed. Then, aging treatment was carried out under protective atmosphere at a temperature of 500°C for 8 hours; the alloy had a tensile strength of 384 MPa, an elongation of 8.1%, a conductivity of 85.4% IACS, a hardness of 122 HV, and a material yield of 44.7%.

[0037] Comparative Example 1

[0038] Electrolytic copper, pure tellurium and Cu-13P master alloy are used as raw materials, and the proportions are as follows: Te: 0.4wt%, P: 0.008wt%, and the balance is Cu. In a graphite crucible, the copper is heated and melted using an induction furnace, and the master alloy of the remaining components is added, and finally the element tellurium is added, and nitrogen is protected. After sufficient stirring, the upper impurities are removed again to purify the melt, and the furnace temperature is controlled at 1350-1450°C. Casting is performed when the temperature of the molten copper alloy is cooled to 1250°C. The copper alloy ingot is subjected to 800°C / 4h homogenization annealing treatment under a protective atmosphere; the homogenized ingot is subjected to 80% cold working deformation treatment; the alloy is then pretreated at 550°C for 1 hour under a protective atmosphere; and then cold deformation processing with a deformation amount of 80% is performed. Then, an aging treatment is carried out under a protective atmosphere at a temperature of 500°C for 8 hours; the alloy has a tensile strength of 271 MPa, an elongation of 5.7%, a conductivity of 92.5% IACS, a hardness of 84 HV, and a material yield of 21.5%.

[0039] Comparative Example 2

[0040] Electrolytic copper and pure tellurium, Cu-24Ce master alloy and Cu-13P master alloy are used as raw materials, and the proportions are Ce: 0.1wt%, Te: 0.4wt%, P: 0.008wt%, and the balance is Cu. In a graphite crucible, the copper is heated and melted using an induction furnace, and the master alloy of the remaining components is added. Finally, the element tellurium is added, and nitrogen is protected. After sufficient stirring, the upper impurities are removed again to purify the melt, and the furnace temperature is controlled at 1350-1450°C. The temperature of the molten copper alloy is cooled to 1250°C for casting. The copper alloy ingot is subjected to homogenization annealing treatment at 800°C for 4h under a protective atmosphere; the homogenized ingot is subjected to cold working deformation treatment with an amount of deformation of 80%; the alloy is then pretreated at 550°C for 1 hour under a protective atmosphere; and then cold deformation processing with an amount of deformation of 80% is performed. Then, an aging treatment is carried out under a protective atmosphere at a temperature of 500°C for 8 hours; the alloy has a tensile strength of 284 MPa, an elongation of 7.8%, a conductivity of 93.4% IACS, a hardness of 89 HV, and a material yield of 34.4%.

[0041] Comparative Example 3

[0042] Electrolytic copper and pure tellurium, Cu-50Zr master alloy and Cu-13P master alloy are used as raw materials, and the proportions are as follows: Zr: 0.2wt%, Te: 0.4wt%, P: 0.008wt%, and the balance is Cu. In a graphite crucible, the copper is heated and melted using an induction furnace, and the master alloy of the remaining components is added, and finally the element tellurium is added, and nitrogen is protected. After sufficient stirring, the upper impurities are removed again to purify the melt, and the furnace temperature is controlled at 1350-1450°C. The temperature of the molten copper alloy is cooled to 1250°C for casting. The copper alloy ingot is subjected to homogenization annealing treatment at 800°C for 4h under a protective atmosphere; the homogenized ingot is subjected to cold working deformation treatment with an 80% deformation amount; the alloy is then pretreated at 550°C for 1 hour under a protective atmosphere; and then cold deformation processing with a deformation amount of 80% is performed. Then, aging treatment was carried out under protective atmosphere at a temperature of 500°C for 8 hours; the alloy had a tensile strength of 302 MPa, an elongation of 12.1%, a conductivity of 94.0% IACS, a hardness of 94 HV, and a yield of 55.4%.

[0043] The performance test methods of the alloy are as follows:

[0044] Tensile strength: After the samples were cut into tensile specimens, they were tested using an MTS 8032 tensile testing machine at room temperature with a tensile rate of 1 mm / min.

[0045] Elongation: Elongation is measured after the sample undergoes a tensile test.

[0046] Conductivity: The samples were cut into 3 mm × 60 mm sheets and the conductivity was measured at room temperature (20°C) using a double-bridge DC resistivity tester. Each sample was tested three times to obtain the average value of the conductivity.

[0047] Hardness: Cut the sample into 3mm×60mm pieces and measure the hardness using HV-1000 Vickers hardness tester with a loading force of 300g and a loading time of 15s. Test each sample 5 times to obtain the average hardness value.

[0048] Yield rate: The final sample is milled after defective parts are cut off, weighed and compared with the mass of raw materials.

[0049] The embodiments of the present invention are described in detail, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations made to these embodiments without departing from the principles and spirit of the present invention still fall within the protection scope of the present invention.

Claims

1. A new copper-tellurium alloy for use in the field of new energy, characterized in that: The copper-tellurium alloy consists of the following components: Te: 0.2-1.5wt%, Ce: 0.1-0.75wt%, Zr: 0.09-0.6wt%, P: ≤0.02wt%, and the balance is Cu.

2. A new copper-tellurium alloy for use in the new energy field as claimed in claim 1, characterized in that: The properties of the copper-tellurium alloy include the following: electrical conductivity greater than 85.4% IACS, hardness greater than 98 HV, tensile strength greater than 297 MPa, elongation greater than 8.1%, and yield greater than 44.7%.

3. A new copper-tellurium alloy for use in the new energy field as claimed in claim 1 or 2, characterized in that: The copper tellurium alloy includes a TeZrCe phase.

4. A low-cost preparation method for a new copper-tellurium alloy for use in the field of new energy as claimed in any one of claims 1 to 3, characterized in that: The method comprises smelting, casting, homogenization and combined deformation heat treatment processes.

5. A low-cost preparation method for a new copper-tellurium alloy for use in the field of new energy as claimed in claim 4, characterized in that: The steps include: (1) Melting: Various element components are prepared in proportion according to the alloy composition, the raw materials are added into a crucible, and after being fully stirred under a protective atmosphere, the upper impurities are removed to purify the melt, and the furnace temperature is controlled at 1250-1400°C to obtain a molten copper alloy; (2) Casting: pouring the molten copper alloy at a temperature of 1250-1350° C.; (3) Homogenization: The copper alloy ingot is subjected to homogenization annealing treatment in a protective atmosphere at a temperature of 700-850°C for 2-5 hours; (4) Combined deformation heat treatment: The homogenized ingot is subjected to cold working deformation treatment with a deformation amount of ≥80%; the alloy is then pretreated at 450-550°C for 1-2 hours under a protective atmosphere; then cold deformation treatment is performed with a deformation amount of ≥75%; then aging treatment is performed under a protective atmosphere at a temperature of 300-500°C for 2-16 hours to obtain a new copper tellurium alloy for use in the new energy field.

6. A low-cost preparation method for a new copper-tellurium alloy for use in the field of new energy as claimed in claim 5, characterized in that: The protective atmosphere in step (1), (3) or (4) is nitrogen.

7. A copper-tellurium alloy obtained by a low-cost preparation method of a new copper-tellurium alloy for use in the new energy field according to any one of claims 4 to 6.

Citation Information

Patent Citations

  • A method for preparing tellurium copper alloy material

    CN110284024B

  • Tellurium-copper alloy for new energy and processing method thereof

    CN112575217A

  • Tellurium-copper alloy strip and preparation method thereof

    CN116083749A

  • Tellurium-containing copper alloy strip and preparation method and application thereof

    CN117568654A